Reconciling DNA replication and transcription in a hyphal organism: visualizing transcription complexes in live Streptomyces coelicolor. Issue 10 (20th August 2019) - Kerr, Leena; Hoskisson, Paul A.
Abstract : Reconciling transcription and DNA replication in the growing hyphae of the filamentous bacterium Streptomyces presents several physical constraints on growth due to their apically extending and branching, multigenomic cells and chromosome replication being independent of cell division. Using a GFP translational fusion to the β ′-subunit of RNA polymerase ( rpoC-egfp ), in its native chromosomal location, we observed growing Streptomyces hyphae using time-lapse microscopy throughout the lifecycle and under different growth conditions. The RpoC-eGFP fusion co-localized with DNA around 1.8 µm behind the extending tip, whereas replisomes localize around 4–5 µm behind the tip, indicating that at the growing tip, transcription and chromosome replication are to some degree spatially separated. Dual-labelled RpoC-egfp/DnaN-mCherry strains also indicate that there is limited co-localization of transcription and chromosome replication at the extending hyphal tip. This likely facilitates the use of the same DNA molecule for active transcription and chromosome replication in growing cells, independent of cell division. This represents a novel, but hitherto unknown mechanism for reconciling two fundamental processes that utilize the same macromolecular template that allows for rapid growth without compromising chromosome replication in filamentous bacteria and may have implications for evolution of filamentous growth in micro-organisms, where uncoupling of DNA replication from cell division is required.